The imaginary number i is defined such that i2 = –1. What does i + i2 + i3 + L + i 23 equal?

NetherCraft 0

The imaginary number i is defined such that i2 = –1. What does i + i2 + i3 + L + i 23 equal?

A. i

B. –i

C. –1

D. 0

E. 1

I’m sorry, there shouldn’t be any “L”, just “…” mark

6 Answers

  • You should memorize this pattern:

    i^1 = i

    i^2 = -1

    i^3 = -i

    i^4 = 1

    And it will keep going as i, -1, -i, 1, i, -1, -i, 1, etc. So any exponent that’s a multiple of 4 will equal 1, and you can figure out the values of non-multiples by counting up or down from the multiple of 4.

    So onto the your math problem!

    i = i

    i^2 = -1

    i^3 = -i

    L = huh?

    i^23 = -i (i^24 is 1. One number before that in the pattern is -i).

    I have no idea what the “L” means, so I will ignore it. If it’s a typo, hopefully you will understand how to do it on your own. It will be pointless for me to continue, since the answer will be different from your choices. But….

    i + i^2 + i^3 + i^23 = i – 1 – i – i

    = -i – 1

    Just add whatever L is supposed to be. And there’s your answer.

  • What is the L standing for? Should this just be a series adding all powers of i from 1 to 23? If so then

    i^2 = -1

    i^3 = -i

    i^4 = 1

    So i + i^2 + i^3 + i^4 = 0

    The same will happen with each succeeding set of four powers. This leaves you with i^21 + i^22 + i^23.

    Can you finish it from there?

  • Define Imaginary Numbers

  • Imaginary Number Definition

  • For the best answers, search on this site https://shorturl.im/W84dx

    =(1 – i^24)/(1 – i) – 1 (geometric series formula) =0 – 1 = – 1 because i^24 = (i^4)^6 = ((i²)²)^6 = ((-1)²)^6 = 1^6 = 1

  • = -1 + L -i ,assuming i 23 means i^23. Have no idea what L is.

Also Check This  qual è il risultato di (x -1)(x-1)(x-1)?

Leave a Reply

Your email address will not be published. Required fields are marked *